INOVASI NILAI TAMBAH KOMODITI PERTANIAN UNGGULAN UNTUK MENINGKATKAN KUALITAS PRODUK PERTANIAN DAN PEMASARAN DI KABUPATEN KONAWE SELATAN - Rianse, Ilma Sarimustaqyma; Sudarmo, Hadi; Awaluddin, Andi; Kusumabaka R., Muhammad Ikbal (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2023)
The potential land area in South Konawe Regency is very good for increasing land use for productive activities in order to support economic growth in the district. The aim of this research is to analyzing product development innovations from coffee commodities in South Konawe Regency. The population of this research is coffee farmers who also carry out post-harvest processing. The sample from this research was the Tolaki Kopindo Sukses Bersama Coffee Home Industry in Landono District, South Konawe Regency, which was determined purposively. Then the sample of farmers was determined using the snowball sampling technique. The data collection methods used are observation methods, survey methods, interview methods and recording methods. The data processing stages carried out include editing, data coding, and tabulating. The analytical method used is Product Development Innovation Analysis. The research results show that innovation in developing coffee products in order to improve the quality of existing coffee products can be done with instant coffee sachets. The development of this coffee product can be done by empowering the UMKM Kopindo Sukses Bersama as a pioneer in processing packaged ground coffee in South Konawe.